GOOGLE CLASS ROOM:DISTANCE LEARNING MEDIA IN THE DANCE CREATION PROCESS - NIKKA KARUNIA MURCI; HENY ROHAYANI; AGUS BUDIMAN (Journal of Dance and Dance Education Studies, 2024)
Until now, the Covid-19 virus pandemic is not over, but all aspects of social life, especially in terms of education, must continue and adapt to the current situation. Various methods are used to carry out online learning processes using the Google Classroom application. The goal to be achieved is to further examine and describe the learning concepts used, the learning process carried out and the learning outcomes obtained by students while participating in this online learning. This research was conducted at SMPN 15 Bandung with the participation of class VIII.2 students. The method used in the research was descriptive qualitative. The research results show that the learning concept is determined by the process of creating learning syntax which is then determined by the online learning process using Google Classroom media and communicating with WhatsApp. In the process of implementing dance learning, it was carried out through virtual Google Classroom classes in five meetings using lecture and dance appreciation methods. The results of dance learning and the responses of class VIII.2 students obtained a level of difficulty that was still standard and according to the student's abilities so that students were able to complete and complete assignments optimally.